Research Progress on Cloning and Function of Xa Genes Against Rice Bacterial Blight - Yang, Yong; Zhou, Yuhang; Sun, Jia; Liang, Weifang; Chen, Xinyu; Wang, Xuming; Zhou, Jie; Yu, Chulang; Wang, Junmin; Wu, Shilu; Yao, Xiaoming; Zhou, Yujie; et al. (Frontiers in Plant Science, 2022)
Bacterial blight (BB) of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most serious bacterial diseases that hinder the normal growth and production of rice, which greatly reduces the quality and yield of rice. The effect of traditional methods such as chemical control is often not ideal. A series of production practices have shown that among the numerous methods for BB controlling, breeding and using resistant varieties are the most economical, effective and environmentally friendly, and the important basis for BB resistance breeding is the exploration of resistance genes and their functional research. So far, 44 rice BB resistance genes have been identified and confirmed by international registration or reported in journals, of which 15 have been successfully cloned and characterized. In this paper, research progress in recent years is reviewed mainly on the identification, map-based cloning, molecular resistance mechanism and application in rice breeding of these BB resistancegenes, and the future influence and direction of the remained research for rice BB resistance breeding is also prospected.